2D nanosheets-based composite materials for supercapacitors - Kong, Xing Yi. (2013)
Efficient energy storage systems are the key to future higher operating demands in a variety of applications such as portable electronics devices and hybrid electric vehicles. Supercapacitor is one of the promising next-generation energy storage devices. Though supercapacitors possess high power capability, their energy densities are still far to be comparable with batteries. Intense research efforts have been attracted in the research of supercapacitors that can yield both high specific power and energy densities. Conducting polymers are one of the spotlight materials for supercapacitors owing to their low-cost, facile synthesis and high capacitance. However, one of the major drawbacks of conducting polymers that hampers its practical use in supercapacitors is poor stability during cycling caused by mechanical degradation of material during the doping/de-doping processes.